Prevalence and Profile of Adolescents with Sexually Transmitted Infections at the Dermatology and Venereology Polyclinic of Ngoerah Hospital, Bali, Indonesia - Intaran, Kadek Devi Aninditha; Elis Indira, I Gusti Ayu Agung; Pemana, Aditya; Puspawati, Ni Made Dwi (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2025)
Background: Sexually Transmitted Infections (STIs) have been considered a public health threat in all countries, both in developed and developing countries. STIs have a direct impact on sexual and reproductive health through stigmatization, infertility, cancer, and pregnancy complications that can increase the risk of HIV. Purpose: This study aims to identify cases of adolescent patients with STIs at Ngoerah Hospital, Denpasar, Bali in the period 2021 to 2023. Methods: This study uses a descriptive observational study with a cross-sectional design. The research was conducted at the Dermatology and Venereology Polyclinic and the Medical Record Installation of Ngoerah Hospital, Denpasar, Bali. After the data was collected, it was tabulated in tabular form and grouped descriptively. Result: A total of 46 patient samples were obtained, with an average age of 16.7 years. Adolescents with STIs were more commonly found in female (63%). Based on their last education, the highest number of patients were junior high school graduates (58.7%) with a history of multipartner sexual intercourse (56.5%). Only 15.2% claimed to be married. The most common type of STIs was syphilis (50%), followed by condyloma acuminata (45.6%). A total of 67.4% of adolescents were known to have HIV-positive status. Conclusion: The picture of STIs in teenagers is more common in female with a junior high school education. Most teenagers have multi-partner partners with a history of having sexual relations with commercial sex workers (CSWs). The most common type of STIs in teenagers is syphilis (50%), and 67.4% are infected with HIV.